Lending Standards and Output Growth - Kirti, Divya (IMF Working Papers; Working Paper ;, 2018)
While some credit booms are followed by economic underperformance, many are not. Can lending standards help separate good credit booms from bad credit booms contemporaneously? To observe lending standards internationally, I use information from primary debt capital markets. I construct the high-yield (HY) share of bond issuance for a panel of 38 countries. The HY share is procyclical, suggesting that lending standards in bond markets are extrapolative. Credit booms with deteriorating lending standards (rising HY share) are followed by lower GDP growth in the subsequent three to four years. Such booms deserve attention from policy makers.